Fibromuscular dysplasia presenting with a deep vein thrombosis. Issue 2 (23rd February 2020) - Lam, Danielle; Jansen, Shirley; Tibballs, Jonathan; McLean-Tooke, Andrew
Abstract : A 41-year-old male patient presented with isolated right lower limb swelling. An ultrasound scan showed right external iliac and femoral vein deep vein thrombosis due to extrinsic compression by an aneurysm of the right common iliac artery. Investigations including imaging and a tissue biopsy of right and left femoral arteries confirmed a rare clinical presentation of fibromuscular dysplasia involving iliac, coeliac, renal and pulmonary vessels. The common iliac artery aneurysm was successfully treated with endovascular repair. Six months later, he developed coronary artery involvement with spontaneous dissection of left anterior descending artery diagnosed on coronary angiogram which was managed conservatively. At 6-year follow-up, he remains clinically asymptomatic and continues with regular surveillance imaging. Iliac arterial fibromuscular dysplasia is uncommon and clinical presentation with a complication such as a deep vein thrombosis is atypical.